OPTIMALISASI KEBUTUHAN LISTRIK PADA KAPAL LANDING CRAFT TANK (LCT) 1500 DWT - Lilis Sofiah (2022)
The ship's electrical installation system is the most important system on the ship in order to distribute electrical energy from the generator to each of the special electrical needs on the ship such as lighting loads, power loads, communication and navigation systems. an imbalance between electricity demand and generator capacity will result in wasteful expenditure of fuel on ships as well as higher maintenance requirements due to insufficient combustion. On the landing craft tank there is a generator power that is large enough so that redesign in the previous study. The purpose of this research is to conduct a study on optimizing the electricity demand on the landing craft tank (LCT) 1500 DWT redesign in previous research by re-selecting the generator power capacity and planning a single line diagram according to the generator capacity power, so that from single line diagram shows the full load ampere to determine the maximum load that can be achieved by the motor. The method used in this research is a planning method based on comparative data. The results of this study indicate the operational needs of the ship based on the condition of the largest ship located on the condition of the ship sailing at night of 102.5 KW. Thus, obtained 2 generators with a power capacity of 52 KW as much as 2 sets. And full load ampere or nominal current is 1 generator of 93.9 A, lighting system of 89.2 A, power system of 256.6 A and communication navigation of 10.8 A.